2015
DOI: 10.1111/jai.12918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sediment burial on grass carp,Ctenopharyngodon idella(Valenciennes, 1844), eggs

Abstract: It is thought that grass carp (Ctenopharyngodon idella) eggs must remain suspended in the water column in order to hatch successfully. Using sand, the effects of varying sediment levels on grass carp eggs were tested at different developmental states and temperatures. Survival was high (15-35%, depending on temperature and trial) in the unburied treatment where eggs rested on a sand bed but were not covered by sediment. Survival was lower in the partial burial (5-10%) and very low (0-4%) in the full burial tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…We do not know the reason for this slower development, but we speculate that it may have been due to crowding or food scarcity. The other two species showed faster development and growth under similar conditions, and were similar to model predictions of developmental rate ( George et al, 2015 ). Silver carp in tanks did not advance past the notochord tip lifting stage (stage 41) during those first two weeks, and bighead and grass carp larvae in tanks achieved stage 43 (two chamber gas bladder) in a similar interval.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…We do not know the reason for this slower development, but we speculate that it may have been due to crowding or food scarcity. The other two species showed faster development and growth under similar conditions, and were similar to model predictions of developmental rate ( George et al, 2015 ). Silver carp in tanks did not advance past the notochord tip lifting stage (stage 41) during those first two weeks, and bighead and grass carp larvae in tanks achieved stage 43 (two chamber gas bladder) in a similar interval.…”
Section: Discussionsupporting
confidence: 74%
“…Horizontal swimming begins as soon as two days after hatch (upon the emergence of the gas bladder). George & Chapman (2013) and George et al (2015) further reported coarsely measured vertical swimming speeds, and water column location for vertical and horizontally swimming grass carp and bigheaded carp larvae.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…nobilis ) which are also considered highly undesirable invaders in the United States and highly beneficial in Asia, can spawn hundreds of thousands of eggs at a time in turbulent flows of large rivers and their tributaries. Eggs subsequently develop and hatch while drifting in the currents [13–15]. Therefore, understanding grass carp and bigheaded carp response to flow and turbulence regimes at early life stages is fundamental to monitoring and controlling their dispersal and drift.…”
Section: Introductionmentioning
confidence: 99%